Construction of alkynyl and acyl disulfides directly through thiol-modification with N-alkynylthio phthalimides under acid catalysis. Issue 8 (24th March 2023) - Xue, Yao-Nan; Feng, Kai; Tian, Jun; Zhang, Juan; Chang, Hong-Hong; Gao, Wen-Chao
Abstract : Acid-catalyzed disulfuration and rearrangement have been disclosed for the construction of alkynyl or acyl disulfides from thiols and N -alkynylthio phthalimides, enabling access to disulfide-modified thiodrugs, thiopeptides and thioglycosides. Abstract : Functionalized disulfides with active sites are valuable for drug release and bioconjugation. In this article, we have developed a novel method for the construction of functionalized disulfides, with alkynyl or acyl groups, directly from readily available thiols under acid catalysis. Alkynylthiolation of thiols, including thiodrugs, thiopeptides and thioglycosides, was efficiently and chemoselectively realized with N -alkynylthio phthalimides catalyzed by TFA, and acyl disulfides were formed via one-pot alkynylthiolation and hydrative oxyarylation under TMSOTf catalysis.